Compressive fatigue behavior of graded tantalum scaffolds produced by electron beam powder bed fusion - Yu Guo; Chao Chen; Weiwei He; Yuankui Cao; Hongtao Xing; Hang Fang; Chen Wu; Kechao Zhou (Journal of Materials Research and Technology, 2023)
In this study, graded tantalum scaffolds were manufactured by electron beam powder bed fusion (EB-PBF). Compression-compression fatigue testing was conducted on the EB-PBF built graded tantalum scaffolds. The compressive fatigue behavior and compressive fatigue strength of graded tantalum scaffolds with vertical gradient (VG) and parallel gradient (PG) states were investigated. In the fatigue testing, the failure of PG graded scaffold was concentrated on the lowest strength constituent, resulting in higher cyclic ratcheting strain and fatigue damage strain. In terms of the VG graded scaffold, due to the simultaneous uniform deformation of each structure, the strain accumulation in a single cycle was small, resulting in the low cyclic ratcheting strain. In addition, the propagation of fatigue cracks in pore structure with higher strength can be retarded by the stress redistribution, resulting in the low fatigue damage strain. Therefore, the design idea of graded pore structure under identical strain condition is beneficial to obtain porous tantalum scaffold with high compressive fatigue strength.